Seroprevalence and risk factors of peste des petits ruminants in different production systems in Uganda - Nkamwesiga, Joseph; Lumu, P.; Nalumenya, D.P.; Korennoy, F.; Roesel, Kristina; Wieland, Barbara; Pérez, A.; Kiara, Henry K.; Muhanguzi, D. (Elsevier, 2023)
Peste des petits ruminants (PPR) is a highly contagious and fatal disease of mostly domestic goats and sheep. First reported in Uganda in 2007, the extent of peste des petits ruminants virus (PPRV) exposure, geographical distribution and risk factors of its transmission and spread are not clearly understood. In this study, we used cluster random sampling methodology to select study villages from three districts representing three different production systems along Uganda’s “cattle corridor”. Between October and December 2022, 2,520 goat and sheep serum samples were collected from 252 households with no history of PPR vaccination in the past one year. The household heads were interviewed to assess possible risk factors of PPRV transmission using a structured questionnaire. The serum samples were screened with a commercial competitive enzyme-linked immunosorbent assay (cELISA) for PPRV antibodies. The determined overall true seroprevalence of PPRV was 27.3% [95% CI: 25.4–29.1]. The seroprevalence of PPRV antibodies in different production systems was 44.1% [95% CI: 40.6–47.7], 31.7% [95% CI: 28.4–35.0] and 6.1% [95% CI: 4.4–7.9] for pastoral, agropastoral and mixed crop-livestock production systems respectively. A mixed-effects multivariable logistic regression model revealed strong statistical evidence of association between female animals and PPRV antibody seropositivity compared to males [OR=2.45, 95% CI: 1.7–3.5, p < 0.001]. The likelihood of being PPRV antibody seropositive significantly increased with increasing small ruminant age. Animals older than 3 years were more than three times as likely to be PPRV seropositive compared to animals aged under 1 year [OR= 3.41, 95% CI: 2.39–4.85, p < 0.001]. There was no statistical evidence of association between small ruminant species and PPRV antibody seropositivity (p = 0.423). Village flocks that interacted with neighboring flocks daily during grazing (IRR = 1.59, 95% CI: 1.19–2.13) and watering around swamps (IRR = 1.59, 95% CI: 1.19–2.13) were highly correlated with increased number of PPRV seropositive animals as compared to flocks that were more restricted in grazing and watered around other water sources other than swamps. Flocks from pastoral and agropastoral production systems were more than 10 times more likely to have seropositive animals than mixed crop-livestock flocks. Targeting PPR control interventions (vaccination and livestock movement control) to pastoral and agro-pastoral small ruminant production systems that are very prone to PPR incursions is recommended to prevent PPRV spread to low-risk smallholder mixed crop-livestock production systems.